HARMONY OF ISLAMIC AND WESTERN PHILOSOPHY IN TRANSDISCIPLINARY DA'WAH: BUILDING A NARRATIVE OF MODERATION IN THE GLOBAL ERA - Surya Eka Priyatna; M. Iqbal; Irfan Noor (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
Da'wah as an activity to convey Islamic values requires an approach that is relevant to the context of the times. In the global era, the challenges faced not only involve theological issues, but also interaction with various cross-cultural thoughts, especially Islamic and Western philosophy. This research aims to integrate the two philosophical traditions through a transdisciplinary approach in order to enrich da'wah methods, especially to build an inclusive narrative of moderation. Using a qualitative approach based on literature study and hermeneutic analysis, this research finds that the concept of wisdom in Islamic philosophy and deliberation in Western philosophy can be synergized as a theoretical basis for moderation-based da'wah strategies. The findings offer a new paradigm in da'wah studies that is not only rooted in Islamic tradition, but also open to dialogue with Western thought. The implications of this research include the development of a da'wah narrative that is able to respond to social polarization and the needs of a multicultural society in the digital era. The proposed transdisciplinary da'wah model is expected to be a significant contribution in building a more inclusive and harmonious cross-cultural communication framework.